Resilience and adaptations—insights from Norwegian adolescents with pediatric-onset spinal cord injury - Höfers, Wiebke; Riiser, Kirsti; Jørgensen, Vivien; Hauger, Solveig L.; Roaldsen, Kirsti Skavberg (Frontiers in Rehabilitation Sciences, 2025)
IntroductionPediatric-onset spinal cord injuries (SCIs) significantly impact adolescents' psychosocial and physical developments, posing unique challenges during a critical period of identity formation and progression toward independence. Despite the rarity of pediatric SCIs, the need for understanding how adolescents adapt to their SCIs is crucial. Thus, the aims of this study were to examine and describe the adaption and returning to daily life of adolescents with pediatric-onset SCIs.MethodsEight adolescents (4 boys and 4 girls) with SCIs who were aged 11–16 years at the time of the injury were interviewed individually 1–6 years post injury using a semi-structured, strength-based thematic interview guide. The interviews were conducted face-to-face (n = 6) or digitally (n = 2). A thematic analysis was used to identify key themes in the transcribed data.ResultsThree key themes were identified. Theme 1, “integrating into social life,” highlighted the importance of supportive social networks, with peers and family playing crucial roles. Theme 2, “finding an identity as an adolescent,” underscored the impact of the disability on the adolescent's identity and pursuit of independence. Theme 3, “gaining a sense of control in life,” illustrated strategies for self-care, socializing, and managing physical and psychological challenges.DiscussionThe adolescents in this study who had pediatric-onset SCI demonstrated resilience, adaptability, and agency in navigating social integration, identity formation, and regaining control over their lives. This study emphasizes the importance of social networks and the desire for autonomy in daily life. The participants' experiences suggest an improvement in their involvement in making decisions concerning themselves and a need to inform health-care professionals and improve support for adolescents during and after rehabilitation.